Using latent semantic analysis (LSA) to study expert design teams' verbal communication - Yeng, Xi (2009)
Teams of people design products. They bring their own language, experiences, perspectives, and detailed knowledge to the design. Thus, design in a team can be regarded as a social process of reaching a “shared understanding”, through activities such as information exchange, compromise and negotiation. Latent Semantic Analysis (LSA) is a computational linguistic technique. It is well known for its ability of modeling human knowledge representations and capturing the latent relations between words and passages. LSA was applied in design team research. Previous research showed that by mining design teams’ formal documentation, LSA can successfully capture different designers’ semantics. Quantification metrics used to measure semantic coherence of design documentation could predict successful design outcomes.